A small molecule CFTR potentiator restores ATP-dependent channel gating to the cystic fibrosis mutant G551D-CFTR - Liu J. (2023)
Background and Purpose: Cystic fibrosis transmembrane conductance regulator (CFTR) potentiators are small molecules developed to treat the genetic disease cystic fibrosis (CF). They interact directly with CFTR Cl− channels at the plasma membrane to enhance channel gating. Here, we investigate the action of a new CFTR potentiator, CP-628006 with a distinct chemical structure. Experimental Approach: Using electrophysiological assays with CFTR-expressing heterologous cells and CF patient-derived human bronchial epithelial (hBE) cells, we compared the effects of CP-628006 with the marketed CFTR potentiator ivacaftor. Key Results: CP-628006 efficaciously potentiated CFTR function in epithelia from cultured hBE cells. Its effects on the predominant CFTR variant F508del-CFTR were larger than those with the gating variant G551D-CFTR. In excised inside-out membrane patches, CP-628006 potentiated wild-type, F508del-CFTR, and G551D-CFTR by increasing the frequency and duration of channel openings. CP-628006 increased the affinity and efficacy of F508del-CFTR gating by ATP. In these respects, CP-628006 behaved like ivacaftor. CP-628006 also demonstrated notable differences with ivacaftor. Its potency and efficacy were lower than those of ivacaftor. CP-628006 conferred ATP-dependent gating on G551D-CFTR, whereas the action of ivacaftor was ATP-independent. For G551D-CFTR, but not F508del-CFTR, the action of CP-628006 plus ivacaftor was greater than ivacaftor alone. CP-628006 delayed, but did not prevent, the deactivation of F508del-CFTR at the plasma membrane, whereas ivacaftor accentuated F508del-CFTR deactivation. Conclusions and Implications: CP-628006 has distinct effects compared to ivacaftor, suggesting a different mechanism of CFTR potentiation. The emergence of CFTR potentiators with diverse modes of action makes therapy with combinations of potentiators a possibility.